“I don’t wanna die, but my brain insists that I should”: a big qualitative data approach to the lived experiences of suicidal thoughts - Marchionatti, Lauro Estivalete; Amaral, Rafael Ramos; Barcellos, Camila; Duarte, Samanta; Campello, André Cardoso; Virtuoso, Eduardo; Magalhães, Pedro Vieira da Silva (Frontiers in Psychology, 2024)
Introduction: There remains a dearth of knowledge concerning the phenomenology of suicidal thoughts, with research focusing on reasons for feeling suicidal rather than their mental expression. While clinical interviews remain the standard phenomenological approach, such exploration of lived experiences may prove challenging for this sensitive topic. As a complementary alternative, the use of naturally-occurring online data is opportune for capturing elaborations on tabooed phenomena. Methods: In this phenomenological study, we present a thematic analysis on lived experiences of suicidal thoughts as spontaneously reported by non-identified users of a Reddit online board (r/Depression), collecting 668 posts using the search terms “suicidal ideation”, “suicidal thoughts”, and “suicide”. Codes were grouped into descriptive categories summarizing the properties of thoughts, their effects, and their relation to suicide. Then, an interpretative synthesis yielded global themes connecting salient meanings on the experience of suicidal thoughts. Results: With a long-term and recurring nature, thoughts of suicide appear in the form of vivid imagery and daydreamings, initially bringing relief to adverse feelings but eventually becoming conditioned and all-consuming. Rather than a ponderment, they are experienced as intrusive thoughts by people struggling to make meaning of their occurrence. When conciliating the presence of unwanted thoughts, users express intricate relations to wishing or not to die, as well as varying perceptions of control over actions or fear of suicidal behaviour. Discussion: With an innovative application of big qualitative data into phenomenological analysis, this study contributes to an initial characterization of suicidal thoughts, uncovering findings that are not contemplated into current conceptualizations of suicidality. The analysis is limited by a restricted context of posts and unknown demographics, and further research with clinical interviews is warranted for in-depth exploration of suicidal thoughts.